International Myeloma Working Group consensus criteria for response and minimal residual disease assessment in multiple myeloma - Kumar, Shaji; Paiva, Bruno; Anderson, Kenneth C; Durie, Brian; Landgren, Ola; Moreau, Philippe; Munshi, Nikhil; Lonial, Sagar; Bladé, Joan; Mateos, Maria-Victoria; Dimopoulos, Meletios; Kastritis, Efstathios; et al. (The lancet oncology, 2016)
Treatment of multiple myeloma has substantially changed over the past decade with the introduction of several classes of new effective drugs that have greatly improved the rates and depth of response. Response criteria in multiple myeloma were developed to use serum and urine assessment of monoclonal proteins and bone marrow assessment (which is relatively insensitive). Given the high rates of complete response seen in patients with multiple myeloma with new treatment approaches, new response categories need to be defined that can identify responses that are deeper than those conventionally defined as complete response. Recent attempts have focused on the identification of residual tumour cells in the bone marrow using flow cytometry or gene sequencing. Furthermore, sensitive imaging techniques can be used to detect the presence of residual disease outside of the bone marrow. Combining these new methods, the International Myeloma Working Group has defined new response categories of minimal residual disease negativity, with or without imaging-based absence of extramedullary disease, to allow uniform reporting within and outside clinical trials. In this Review, we clarify several aspects of disease response assessment, along with endpoints for clinical trials, and highlight future directions for disease response assessments.